Description of Idaea josephinae sp. n. from the Iberian Peninsula (Lepidoptera: Geometridae) - Guerrero, Juan-Jose; Hausmann, Axel; Ortiz, Antonio S. (Zootaxa, 2021)
Idaea josephinae sp. n. is described from the Iberian Peninsula. Differential characters from its North African sister species Idaea lobaria (Chrétien, 1909) in external appearance and genitalia, and in the 5’ barcode fragment of the mitochondrial COI gene (the DNA barcode) are presented.